GWAs Identify DNA Variants Influencing Eyebrow Thickness Variation in Europeans and Across Continental Populations - Peng, Fuduan (2023)
Natural variation in eyebrow thickness (ET) is one of the most conspicuous facial32 features. Understanding its genetic basis is of broad interest and has implications for33 dermatology and other fields. Two genome-wide association studies (GWASs) for ET34 have been reported thus far. In 2,457 Latin Americans from the CANDELA cohort,35 Adhikari et al. identified 3q22.3 harboring FOXL2 (Adhikari et al., 2016). In 2,96136 Han Chinese from the TZL cohort, Wu et al. discovered 3q26.33 harboring SOX2 and37 5q13.2 harboring FOXD1 and by meta-analysis of CANDELA and TZL 2q12.338 harboring EDAR (Wu et al., 2018). Thus, four ET-associated loci have been39 established thus far, all in non-Europeans. As no European ET GWAS had been40 reported, it remains unknown whether the genetic ET effects described in non-41 Europeans persist in Europeans, or whether there are European-specific genetic loci42 involved in ET, or both.43 Here, we report the first GWAS of ET in Europeans using 9,948 individuals from44 four cohorts of European ancestry, including the Rotterdam Study (RS, n=4,441),45 TwinsUK (n=1,159, females only), the Queensland Institute of Medical Research46 study (QIMR, n=2,257), and a cohort from the United States (US, n=2,121, Table S1,47 Figure S1, Supplementary Materials).